Hospitalizations for Infective Endocarditis in Children: 15-Year Analysis - Margarida Dias; Rita Amorim; Ana Luísa Correia; Marisa Pereira; Ana Correia-Costa; Ana Reis-Melo; Margarida Tavares (Acta Médica Portuguesa)
Introduction: Infective endocarditis (IE) is a challenging diagnosis with high morbidity and mortality. The aim of this study was to provide a comprehensive analysis of hospitalizations for infective endocarditis in pediatric population at a tertiary hospital. Methods: A retrospective study examining hospitalizations for IE in pediatric population between 2008 and 2022 at Centro Hospitalar Universitário de São João - Unidade Local de Saúde São João, EPE was conducted. Clinical presentation, treatment, complications, and outcomes of IE, as well as underlying microorganisms were reviewed. Results: During this period, there were 27 hospitalizations for IE in children. In recent years, an increase in hospitalizations due to infective endocarditis has been observed, with the number fluctuating between zero and two per year from 2008 to 2017, and between one and five per year from 2018 to 2022. The mean age was 9.2 years (± 5.8), the length of hospitalization had a mean duration of 44 days (± 25.4) with a maximum of 113 days, and two deaths occurred. Heart disease was present in 88.9% (n = 24) of patients, of which 95.8% (23/24) was congenital, 59.3% (16/27) of the patients had prosthetic material and, of these, 18.8% (3/16) had a mechanical valve. Regarding diagnosis, 33.3% of patients had no vegetation in imaging tests. In 25.9% of cases, positron emission tomography was performed. Complications occurred in 51.9% of patients, with 44.4% having cerebral or pulmonary emboli. Regarding underlying organisms, Staphylococcus aureus (48.1%), Staphylococcus epidermidis (14.8%), and Streptococcus (14.8%) were the most frequent. One patient had a culture-negative IE. The mean duration of antibiotic therapy was 6.8 weeks, and 29.6% (8/27) underwent surgery. Conclusion: Throughout the study period, our hospital observed a trend towards an increase in hospitalizations for infective endocarditis in the pediatric population. Streptococci are still described as the most prevalent etiology, but Staphylococci are known to become more frequent, as shown in our sample. Awareness of IE in patients with heart disease and implanted prosthetic material is crucial.